Improving The Average Session Evaluation Score Of Supervisory Programby Using PDCA Cycle At PT XYZ - Jonny Jonny (The Winners, 2016)
PT XYZ took People Development tasks as important things in order to provide great leaders for handling its business operations. It had several leadership programs such as basic management program, supervisory program, managerial program, senior management program, general management program, and the executive program. For basic management and supervisory programs, PT XYZ had appointed ABC division to solely handled them, while the rest, ABC division should cooperate with other training providers who were reputable in leadership ones. The aim of this study was to ensure that the appropriate leadership style has been delivered accordingly to the guideline to the employees by ABC division to improve the average session evaluation score of the supervisory program by using PDCA (Plan, Do, Check, and Action) cycle. The method of this research was by gathering quantitative and qualitative data by using session and program evaluation format to see current condition. The research finds that the reasons why the program is below target 4,10 score. It is related to the new facilitator, no framework, and teaching aids.